The Rise of China and Labor Market Adjustments in Latin America - Artuc, Erhan; Lederman, Daniel; Rojas, Diego (World Bank Group, Washington, DC, 2015)
This paper assesses the impact of the rise of China on the trade of Latin American and Caribbean economies. The study proposes an index to measure the impact on trade, which suggests sizable effects, especially in Argentina, Brazil, Chile, Honduras, Mexico, and Paraguay. The paper uses the index and a model of labor mobility, to calculate the impact of China's growth on labor markets in Argentina, Brazil, and Mexico. The resulting evidence suggests that the rise of China has had positive effects on agriculture and mining in Argentina and Brazil, which offset negative impacts on manufacturing industries, thus leaving total employment and real wages virtually unchanged in the long run. In contrast, the estimated impacts of China's rise on Mexico imply that the sizable shock to manufacturing was not offset by the positive shocks on mining and agriculture, reducing employment in the long run. The paper also discusses the effect of China on the degree of informality in these three economies and contrasts short-run and long-run effects on employment and wages across industries.